Experimental and numerical study of low-damage self-centering precast concrete frame connections with replaceable dampers. (1st October 2020) - Li, Yadong; Geng, Fangfang; Ding, Youliang; Wang, Libin
Highlights: Replaceable and upgradeable dampers are incorporated with the self-centering system. The precast components are almost in the state of no damage. The shear transfer of connection has multiple ways and is more reliable. The stress level of the reinforcements of the novel joint is far lower than the RC joint. The stiffness degradation of the novel joint after the earthquake is very slight. Abstract: A kind of low-damage self-centering precast concrete (LDSCPC) frame connection with replaceable dampers was proposed. Precast components with embedded steel connectors were assembled by unbonded post-tensioned (PT) tendons, and the modular energy dissipation devices made them have great upgrading and expanding capacity. Based on the cyclic load tests of three specimens of LDSCPC frame joint and one specimen of RC frame joint, the influence of initial PT force, location of PT tendons and contribution of dampers on the mechanical performance of LDSCPC joint and the significant difference with RC joint were studied. The test results showed that the load-displacement behavior of the LDSCPC joint presented two-stage characteristics, with the excellent self-centering ability and stable mechanical properties. The stress level of the precast beam of the LDSCPC joint at 3% chord rotation could reach the stress level that of the RC joint at 0.25% chord rotation, and only a few 0.08 mm wide cracks appeared on the concrete surface. The precast components were at lower stress levels and had excellent low damage characteristics. The elaborate solid-element FE model was established, and the results of numerical simulation proved the behavior and characteristics of the LDSCPC joint in the experiment. The parametric study related to the damper was carried out, and some design comments and suggestions were also made.